KONTRIBUSI PENDAPATAN IBU RUMAH TANGGA TERHADAP PENDAPATAN KELUARGA (STUDI KASUS PEMETIK TEH DI DESA AIR SEMPIANG KABUPATEN REJANG LEBONG) - Sumantri, Bambang; Ansori, Budi (Jurnal AGRISEP, 2004)
The objective  of this study was to describe housewives motivation  to work as tea gathers, and analyze their income  contJibution,  and measure  a correlation  of housewives  income  with  family  income.  The first  and second objectives were analysed using descriptive analysis while the last objective used chi-squares analysis. The study  conducted  in Air Sempiang,  Kepahiang distJict, Bengkulu Province.  This research concluded that an economic  reason such as increasing  family income, having personaf income,  fulfilling household needs were  the main reason   motivating  housewifes  to work.  While social motivation,  namely as employing  theirwaste time, making a friend and culture motivation  is another reason. Housewife has ontJibuted 24,85 % of total family income.   The research also found that there was a strong correlation between housewife income and her total family income.